Inhibition of MEK1 Signaling Pathway in the Liver Ameliorates Insulin Resistance - Atsunori Ueyama; Nobuhiro Ban; Masanori Fukazawa; Tohru Hirayama; Minako Takeda; Tatsuo Yata; Hiroyasu Muramatsu; Masaki Hoshino; Marii Yamamoto; Masao Matsuo; Yuka Kawashima; Tatsuhiko Iwase; et al. (Journal of Diabetes Research)
Although mitogen-activated protein kinase kinase (MEK) is a key signaling molecule and a negative regulator of insulin action, it is still uncertain whether MEK can be a therapeutic target for amelioration of insulin resistance (IR) in type 2 diabetes (T2D) in vivo. To clarify whether MEK inhibition improves T2D, we examined the effect of continuous MEK inhibition with two structurally different MEK inhibitors, RO5126766 and RO4987655, in mouse models of T2D. RO5126766 and RO4987655 were administered via dietary admixture. Both compounds decreased blood glucose and improved glucose tolerance in doses sufficient to sustain inhibition of extracellular signal-regulated kinase (ERK)1/2 phosphorylation downstream of MEK in insulin-responsive tissues in db/db mice. A hyperinsulinemic-euglycemic clamp test showed increased glucose infusion rate (GIR) in db/db mice treated with these compounds, and about 60% of the increase was attributed to the inhibition of endogenous glucose production, suggesting that the liver is responsible for the improvement of IR. By means of adenovirus-mediated Mek1 shRNA expression, we confirmed that blood glucose levels are reduced by suppression of MEK1 expression in the liver of db/db mice. Taken together, these results suggested that the MEK signaling pathway could be a novel therapeutic target for novel antidiabetic agents.